2017
DOI: 10.1080/21688370.2017.1382671
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of tight junction transmembrane proteins: Many sites, much to do

Abstract: Phosphorylation is a dynamic post-translational modification that can alter protein structure, localization, protein-protein interactions and stability. All of the identified tight junction transmembrane proteins can be multiply phosphorylated, but only in a few cases are the consequences of phosphorylation at specific sites well characterized. The goal of this review is to highlight some of the best understood examples of phosphorylation changes in the integral membrane tight junction proteins in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 107 publications
1
48
0
Order By: Relevance
“…Tight junctions are made up of a number of protein elements, including transmembrane claudins (total of 27 mammalian claudins), as well as myelin and lymphocyte (MAL) and related proteins for vesicle trafficking and membrane link (MARVEL) [13][14][15][16][17][18]. MARVEL domain-containing proteins are a component of a larger group of tight junction-associated MARVEL proteins (TAMPS) that include transmembrane proteins such as occludin and tricellulin [18][19][20]. Other tight junction-associated transmembrane molecules include junctional adhesion molecules (JAM-1, -2, and -3) that can regulate the formation of tight junctions and migration of neutrophils [21][22][23][24][25][26].…”
Section: Tight Junction Protein Structurementioning
confidence: 99%
“…Tight junctions are made up of a number of protein elements, including transmembrane claudins (total of 27 mammalian claudins), as well as myelin and lymphocyte (MAL) and related proteins for vesicle trafficking and membrane link (MARVEL) [13][14][15][16][17][18]. MARVEL domain-containing proteins are a component of a larger group of tight junction-associated MARVEL proteins (TAMPS) that include transmembrane proteins such as occludin and tricellulin [18][19][20]. Other tight junction-associated transmembrane molecules include junctional adhesion molecules (JAM-1, -2, and -3) that can regulate the formation of tight junctions and migration of neutrophils [21][22][23][24][25][26].…”
Section: Tight Junction Protein Structurementioning
confidence: 99%
“…Posttranslational modification of tight junction proteins is responsible for tight junction function . ERK activation regulates the expression and distribution of tight junction proteins .…”
Section: Resultsmentioning
confidence: 99%
“…Loss of ZO‐1 disrupts claudins formation and localization and subsequently alters barrier function . Phosphorylation modification at the C‐terminus of claudins or occludin may affect protein interaction, distribution, and stability . Kale et al demonstrated that tyrosine phosphorylation of occludin disrupts its association with ZOs .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations